2008
DOI: 10.1016/j.actbio.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Extended interaction of β1 integrin subunit-deficient cells (GD25) with surfaces modified with fibronectin-derived peptides: Culture optimization, adhesion and cytokine panel studies

Abstract: The modification of biomaterials with extracellular matrix-mimicking factors to influence the cellular response through mainly integrin-mediated signaling is a common technique. The inherent limitations of antibody-inhibition studies necessitate the use of complementary methods to block integrin function to confirm cell-surface interaction. In this study, we employed a β1 integrindeficient cell line, GD25, to investigate the role of β1 subunit in cell adhesion and subsequent cytokine (granulocyte macrophage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…N‐hydroxysuccinimide activated esters were prepared from PEGdiol (2k) as previously described 22. All starting materials were purchased from Aldrich unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…N‐hydroxysuccinimide activated esters were prepared from PEGdiol (2k) as previously described 22. All starting materials were purchased from Aldrich unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…Ligand-PEG-grafted gelatin synthesis: PEG-diol modification to Bis-N-hydroxysuccinimide-PEG and Ligand-PEG grafting to gelatin N-hydroxysuccinimide activated esters were prepared from PEGdiol (2k) as previously described. 22 All starting materials were purchased from Aldrich unless otherwise specified. First, bis-t-butylacetate-PEG (Bis-tBuOAc-PEG) was prepared by activating PEG with sodium hydride and then by reacting it with t-butyl bromoacetate for 24 h. T-butyl bromoacetate was filtered and extracted to remove impurities and analyzed by 1 H NMR.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of experiments have already demonstrated that many physical factors such as mechanical property of extracellular matrices/substrates and spatial arrangement of integrin ligands (i.e, RGD peptides), can remarkably regulate initial cell adhesion and subsequent formation of mature focal adhesions (FAs) on extracellular matrices/substrates [2][3][4][5][6][7][8][9][10][11][12][13][14]. For instance, it has been recognized that substrate rigidities are able to upregulate the dynamics of cell adhesion nucleation to some extent owing to that it can promote chemical affinity of integrin receptors by mechanically changing the molecules from bent to extended conformations [8,9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among cell responses to different nanopatterns, a porous surface involving nanotubes has recently received attention. Nanotubes improve osteoblast attachment, function, and proliferation [27] and exhibit very low immunogenicity, eliciting low levels of monocyte activation and cytokine secretion [31]. They may be used in vascular applications to enhance endothelial cell extracellular matrix (ECM) production and motility [15].…”
Section: Introductionmentioning
confidence: 99%